EFFORTS TO IMPROVE THE COMPETENCE OF STRENGTHENING TEACHER CAPACITY AND EDUCATION PERSONNEL THROUGH BINTEK IN SMA NEGERI 1 SERBA JADI - Budi Suhartono (JURNAL TARBIYAH, 2021)
The purpose of this study was to determine the efforts in improving of teacher capacity and education personnel in SMAN 1 Medan, focus on the manufacture of Dupak, Piki and Bandicam. The method used and the reason for the variation of the phenomenological approach. The research method is how to do something by using a mind carefully to achieve the objectives in the study. The finding stated that the activities of making Dupak, Piki and Bandicam have benefits among the teachers